Dramaturgi Peluncuran Danantara dan Dampaknya terhadap IHSG dalam Perspektif Politik Ekonomi - Rusli, Urisnawati; Masnia, Masnia; Darmawati, Darmawati; Rasyid, Syarifuddin (Forum Kerjasama Pendidikan Tinggi, 2025)
This study analyzes the launch of the Indonesian Sovereign Wealth Fund, Daya Anagata Nusantara Investment Authority (Danantara), through Erving Goffman's dramaturgical approach, focusing on its impact on the Indonesia Stock Exchange Composite Index (IHSG). Using a qualitative method, the study identifies the government's narrative through the